PENEGAKAN HUKUM DI PERBATASAN WILAYAH UDARA NEGARA KESATUAN REPUBLIK INDONESIA - Paminto W., Andre; Wahyudi, Misran (Fakultas Hukum Universitas Mahasaraswati Denpasar, 2016)
Each country has sovereignty intact and filled up the air space above its territory, while the border region of the country air stretched over land and over the territorial waters. This research aims to find out how the nature of the regulation concerning the national sovereignty of air space as well as the implementation of law enforcement on the border violations in the Indonesian national airspace by foreign aircraft. The results of this paper are: That the sovereignty of air space is political independence of any state that can not be contested, so that all activities across borders another country must obtain permission from the relevant country. Law enforcement against violations of national airspace on the border of Indonesia conducted by foreign aircraft can not be completed because of the limitations of the main tool air weapons systems.